Coping Strategies for Food Safety Public Opinion Crises in the Era of Omnimedia - CHEN Hui, LUO Jie (Shipin Kexue, 2025)
In the omnimedia era, food safety public opinion spreads rapidly, widely and interactively, thereby easily triggering public panic and trust crises. This paper provides an in-depth analysis of the characteristics, roots, and evolutionary mechanism of food safety public opinion crises and discusses their formation mechanism from various perspectives such as information dissemination, public psychology, and Maslow’s hierarchy of needs. Drawing on the experience of food safety public opinion management in the United States, this paper proposes coping strategies such as rapid response, humble attitudes, empathy, and proper guidance and puts forward suggestions for enhancing the ability to respond to food safety public opinion crises.